Micro-credentials in language education: a study of student satisfaction with e-Safar Sa’īd: the wonders of Malaysia course - Othman, Suzzana; Che Mat, Azman; Saja, Ijlal; Ahmad Fesol, Siti Feirusz (Penerbit UiTM (UiTM Press), 2026)
Micro-credentials have become an increasingly popular way to support flexible and modular learning, yet their role in language education particularly Arabic has not been widely examined. This study explored student satisfaction with e-Safar Sa’īd: The Wonders of Malaysia, an Arabic micro-credential offered through UiTM’s UFUTURE platform. A total of 112 undergraduates participated in a survey that measured perceptions of course relevance and usability, satisfaction across the four key language skills, and overall experience with the programme. The findings show that students responded positively, with average ratings across dimensions ranging from 3.96 to 4.18 on a five-point scale. Reading was rated highest (M = 4.14), followed closely by listening, while speaking and writing were rated somewhat less favorably. Overall satisfaction was strong (M = 4.14) and a majority of respondents said that they would recommend the course to others. Reading satisfaction was the most significant predictor of overall satisfaction for regression analysis (β = 1.10, p < .001) and therefore authentic reading tasks (e.g., signage, menus and tourism texts) can give learners a consistent sense of progress and relevance. The findings point to the promise of Arabic micro-credentials in higher education. Future research may address the need for more integration of writing components and literacy-focused tasks with oral practice.